2012
DOI: 10.1007/s00277-011-1377-y
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome inhibitor bortezomib targets cell cycle and apoptosis and acts synergistically in a sequence-dependent way with chemotherapeutic agents in mantle cell lymphoma

Abstract: Single-agent bortezomib, a potent, selective, and reversible inhibitor of the 26S proteasome, has demonstrated clinical efficacy in relapsed and refractory mantle cell lymphoma (MCL). Objective response is achieved in up to 45% of the MCL patients; however, complete remission rates are low and duration of response proved to be relatively short. These limitations may be overcome by combining proteasome inhibition with conventional chemotherapy. Rational combination treatment and schedules require profound knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
(47 reference statements)
2
23
0
2
Order By: Relevance
“…Table III from our proteomics study indicates that PEO1CarbR cells expressed the highest level of this protein, which may go some way to explaining the preferential sensitisation effect we saw in this cell line (Figure 2). Moreover, the same study demonstrated synergy between chemotherapy and bortezomib, lending support to our findings (41).…”
Section: D-ge Proteomicssupporting
confidence: 88%
See 1 more Smart Citation
“…Table III from our proteomics study indicates that PEO1CarbR cells expressed the highest level of this protein, which may go some way to explaining the preferential sensitisation effect we saw in this cell line (Figure 2). Moreover, the same study demonstrated synergy between chemotherapy and bortezomib, lending support to our findings (41).…”
Section: D-ge Proteomicssupporting
confidence: 88%
“…Like many targeted therapies, bortezomib has reported 'off-target' effects. The eukaryotic initiation factor 4A-1 (EIF4E1) has been shown to be targeted by bortezomib in haematological malignancies, giving rise to G 2 M blockade (41). Table III from our proteomics study indicates that PEO1CarbR cells expressed the highest level of this protein, which may go some way to explaining the preferential sensitisation effect we saw in this cell line (Figure 2).…”
Section: D-ge Proteomicsmentioning
confidence: 73%
“…For instance, bendamustine has shown good results in combination with rituximab (Rummel et al, 2013) or with cytarabine and rituximab (R-BAC) in MCL patients not eligible for intensive therapy (Visco et al, 2013) (100% ORR, 95% CR). The synergy of the proteasome inhibitor bortezomib and cytarabine has been reported in two case reports (Weigert et al, 2007) and in MCL cell lines (Weigert et al, 2007;Hutter et al, 2012). The synergy of the proteasome inhibitor bortezomib and cytarabine has been reported in two case reports (Weigert et al, 2007) and in MCL cell lines (Weigert et al, 2007;Hutter et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…BTZ has been shown to induce apoptosis, [1416] to arrest cell proliferation,17,18 inhibit angiogenesis,19,20 and disrupt the cell-cycle in cancer cells [15, 21, 22]. BTZ's contribution to apoptosis in lymphoma depends on the transcription regulation and/or inhibition of the proteasome degradation of various anti- or pro-apoptotic proteins [8].…”
Section: Introductionmentioning
confidence: 99%